Women, Business and the Law 2018 - World Bank Group (Washington, DC: World Bank, 2018)
How can governments ensure that women have the same employment and entrepreneurship opportunities as men? One important step is to level the legal playing field so that the rules for operating in the worlds of work and business apply equally regardless of gender.